Origin and development of Unani medicine: an analytical study - Arshad Islam, Islam (International Islamic University Malaysia, 2018)
This study traces the history of the origin and development of Unani medicine in the Islamic world and its later flowering in Persia. Based mainly on Arabic, Persian, Urdu and English sources, the study focuses on the intellectual legacy of the Muslims in the development of Unani medicine and their interest in the progress of medical sciences, when a number of classical works were produced by great Muslim scholars during this period that provide evidence of organized medical care that provided the basis for modern medicine as it emerged from the 17th century onwards in Europe. The early Muslim scholars’ works were focused on the integration or Islamicisation of human knowledge in the areas of medical and health-care sciences as well as those who seek to understand the role of moral values and Maqasid al-Shariáh (‘objectives of Sharia) in medical and healthcare practices in a more comprehensive framework, exposing the dynamic contribution of Islamic civilization to medical progress that was later obscured in modernity by Western ideologies.